Mucosal lesions associated with the use of dental prostheses in elderly patients - Yoel González Beriau; Libet Marrero Santana (Medisur)
Background: The quality of the dental prosthesis and its role in the appearance of oral lesions, especially in the elderly, is of special interest for the etiology understanding of these diseases and the preventive strategies recommendation. Objectives: to characterize the geriatric population with lesions in the oral mucosa associated with the use of dental prostheses. Methods: descriptive study, which included all patients (N=48) with dental prostheses who presented mucosal lesions, who attended the dental prosthesis consultation, at the Specialty Stomatology Clinic, in Cienfuegos, from January to June 2020. The analyzed variables were: age, sex, oral lesions, time of use of the prosthesis, habit of use and technical status. Results: lesions in women predominated, with 70.9%. The most affected age group, 65-69 years, with 45.4%. Subprosthesis stomatitis represented 90.2% of all lesions, followed by fissured epulis (7.8%). The presence of injury was associated in 54.5% of cases with a time of use of 5-9 years. The continuous use and presence of maladjusted prostheses were evidenced more frequently, represented in 76.4% and 70.9%, respectively. Conclusion: issues such as prolonged use time, maladjusted prosthesis and continuous use of these are characteristic in this population group, which are logically related to the presence of mucosal lesions.